Decay of photo-excited conductivity of Er-doped SnO2 thin films - Morais, Evandro A.; Scalvi, Luis Vicente de Andrade [UNESP] (Springer, 2007)
Er-doped SnO2 thin films, obtained by sol-gel-dip-coating technique, were submitted to excitation with the 4th harmonic of a Nd:YAG laser (266 nm), at low temperature, and a conductivity decay is observed when the illumination is removed. This decay is modeled by considering a thermally activated cross section of an Er-related trapping center. Besides, grain boundary scattering is considered as dominant for electronic mobility. X-ray diffraction data show a characteristic profile of nanoscopic crystallite material (grain average size approximate to 5 nm) in agreement with this model. Temperature dependent and concentration dependent decays are measured and the capture barrier is evaluated from the model, yielding 100 meV for SnO2:0.1% Er and 148 meV for SnO2:4% Er.